KLIENTALISME BROKER ANTARA ELIT BALADIKA BALI DAN ELIT PDIP DALAM PILGUB 2018 - Rai Dwipayana, I Gusti Ngurah; Ali Azhar, Muhammad; Mahaswari J.M, A.A.Sagung Mirah (Jurnal Nawala Politika, 2019)
After the end of the new order regime, the existence of community groups made it a necessity in a democratic country. The presence of community group the local electoral in Bali in particular is able to provide its own color. Bali governor election 2018 became a separate stage for the contestation between Baladika Bali and PDIP to consolidate their power. With the Patron-Client Theory approach, this research presents as a description of how the actions carried out by CSOs with a background of violence in fighting over the land of power, and of course the status of power. Dynamic politics makes this phenomenon polarized in diverse manifestations. There is a cultural connection, but there also involves a broker in it. Research using ethnographic qualitative methods or field research. The results of this study explain that the clientelism relationship that occurs is a remuneration for assistance given by Patron to Clients. Keywords :Broker, Baladika, PDIP, Bali Governor Election 2018.